The Impact of Training on Worker Performance - Riyadi Nugroho (International Journal of Management Research and Economics, 2023)
We intend to gain further insight into the impact of staff performance training at PT. Inti Graphics Surabaya through this investigation. The sample count consisted of 52 employees. Data were gathered through the use of questionnaires, interviews, and observation techniques. To analyze the data, SPSS (Statistical Product and Service Solution) is used, which is the fundamental analysis of linear regression. The results of the testing include measures to improve and develop employees' attitudes, behaviors, abilities, and knowledge in accordance with the objectives of the relevant agency. The study's conclusions indicate a substantial correlation between employee performance and training.